Bee venom phospholipase A2 suppresses allergic airway inflammation in an ovalbumin‐induced asthma model through the induction of regulatory T cells. Issue 4 (9th August 2015) - Park, Soojin; Baek, Hyunjung; Jung, Kyung‐Hwa; Lee, Gihyun; Lee, Hyeonhoon; Kang, Geun‐Hyung; Lee, Gyeseok; Bae, Hyunsu
Abstract: Bee venom (BV) is one of the alternative medicines that have been widely used in the treatment of chronic inflammatory diseases. We previously demonstrated that BV induces immune tolerance by increasing the population of regulatory T cells (Tregs) in immune disorders. However, the major component and how it regulates the immune response have not been elucidated. We investigated whether bee venom phospholipase A2 (bvPLA2) exerts protective effects that are mediated via Tregs in OVA‐induced asthma model. bvPLA2 was administered by intraperitoneal injection into control and OVA‐challenged mice. The Treg population, total and differential bronchoalveolar lavage fluid (BALF) cell count, Th2 cytokines, and lung histological features were assessed. Treg depletion was used to determine the involvement of Treg migration and the reduction of asthmatic symptoms. The CD206‐dependence of bvPLA2‐treated suppression of airway inflammation was evaluated in OVA‐challenged CD206 ‐/‐ mice. The bvPLA2 treatment induced the Tregs and reduced the infiltration of inflammatory cells into the lung in the OVA‐challenged mice. Th2 cytokines in the bronchoalveolar lavage fluid (BALF) were reduced in bvPLA2‐treated mice. Although bvPLA2 suppressed the number of inflammatory cells after OVA challenge, these effects were not observed in Treg‐depleted mice. In addition, we investigated the involvement of CD206 in bvPLA2‐mediated immune tolerance in OVA‐induced asthma model. We observed a significant reduction in the levels of Th2 cytokines and inflammatory cells in the BALF of bvPLA2‐treated OVA‐induced mice but not in bvPLA2‐treated OVA‐induced CD206 ‐/‐ mice. These results demonstrated that bvPLA2 can mitigate airway inflammation by the induction of Tregs in an OVA‐induced asthma model. Abstract : bvPLA2, as a modulator of Treg population, suppresses allergic inflammation in OVA‐induced asthma model. bvPLA2‐induced Treg recruitment to the lungs is correlated with CD206 to ameliorate allergic inflammation.